AIR MICROBIOLOGY CONTENT IN ULEE LHEUE PORT CITY BANDA ACEH - Nadilla Rahima; Junaidi, Junaidi (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The background Indoor air quality greatly affects human health, because 90% of human life is indoors. Good indoor air quality is defined as air that is free of irritating contaminants. At the port itself, many people go back and forth and roam in the waiting room, Microorganisms will come out of their hosts (humans or animals or plants), due to coughing, sneezing, dry body fluids, or due to spores (fungus). The spread of microorganisms in the air can stick to two media, namely solid particulates (dust) and water, where it can occur indoors and outdoors. The purpose of the study was to determine the microbiological content of the air at Ulee Lheue Port, Banda Aceh City. Knowing the number of bacterial colonies and types of bacteria. This research is a descriptive analytical research method. Research data obtained from the calculation of the number of colonies trapped in Na Agar. The results showed that the number of bacterial colonies in the air in 6 rooms at Ulee Lheue Harbor ranged from 11-35 CFU/m3. And the type of bacteria is Bacillus sp. It can be concluded that at the Port of Ulee Lheue the bacterial colony of Bacillus sp in the air is still below the threshold set by the Minister of Health of the Republic of Indonesia No. 1077 of 2011.